Nitrate Derived From Beetroot Juice Lowers Blood Pressure in Patients With Arterial Hypertension: A Systematic Review and Meta-Analysis - Benjamim, Cicero Jonas R.; Porto, Andrey Alves; Valenti, Vitor Engrácia; Sobrinho, Andressa Crystine da Silva; Garner, David M.; Gualano, Bruno; Bueno Júnior, Carlos Roberto (Frontiers in Nutrition, 2022)
Background Although there are a considerable number of clinical studies on nitrate (NO3) rich beetroot juice (BRJ) and hypertension, it is difficult to indicate the real effects of NO3 from BRJ on the BP of hypertensive patients because there are still no estimates of the effects of NO3 derived from BRJ on the BP of hypertension patients. Objective To clarify these effects, we developed a systematic literature review with a meta-analysis of randomized clinical trials (RCTs). Design The searches were accomplished through EMBASE, Cochrane Library, MEDLINE, CINAHL, Web of Science, and LILACS databases. The study included single or double-blinded RCTs and participants older than 18 years with hypertension [systolic BP (SBP) > 130 mmHg and diastolic BP (DBP) > 80 mmHg]. NO3 BRJ was required to be consumed in a format that possibly blinded participants/researchers. These studies should also report the SBP and DBP values (mmHg) measured before and after the treatment. Risk of Bias tools and GRADE were enforced. Results Seven studies were included (218 participants). BRJ intervention time ranged from 3 to 60 days with daily dosages of 70–250 mL of BRJ. After the intervention with NO3 from BRJ, SBP underwent significant changes (p < 0.001) of −4.95 (95% CI: −8.88; −1.01) (GRADE: ⊕⊕⊕○ Moderate), but not for DBP (p = 0.06) −0.90 mmHg (95% CI: −3.16; 1.36) (GRADE: ⊕⊕⊕○ Moderate), compared to the control group. Conclusions The NO3 derived from BRJ reduces SBP, but not DBP in patients with arterial hypertension. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=269339.